FORMULASI SEDIAAN LIP BALM YANG MENGANDUNG EKSTRAK ETANOL DAUN KOPI ARABIKA (Coffea arabica L.) SEBAGAI PELEMBAB BIBIR - Julia Susanti; Utama, Rezza Fikrih; Wilson Sembiring, Antonius (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Lip balm is a preparation that is applied to the lips and functions as a moisturizer by forming an immiscible oil layer on the surface of the lips. Arabica coffee plants contain phenolic and flavonoid compounds that act as antioxidants and flavonoids are also considered to protect the body from the effects of free radicals and environmental pollution which are good for the lips. The purpose of this study was to formulate lip balm using Arabica coffee leaf extract and to evaluate its effectiveness as a lip balm. Arabica coffee leaves were extracted by maceration using 96% ethanol solvent and concentrated with a rotary evaporator. Arabica coffee leaf extract was formulated with concentrations, 5%, 7.5%, and 10%, as a blank used lip balm base. Tests on lip balm preparations include organoleptic tests, homogeneity tests, pH measurements, strength tests, melting point tests, irritation tests and stability tests for preparations with parameters such as odor, color and pH during 28 days of storage. Testing the ability of the preparation to moisturize using a skin analyzer once a week for 28 days. The results showed that all lip balm preparations were homogeneous, had a pH of 5.6-6.2 and were stable for 12 weeks of storage. The preparation of pomegranate peel extract lip balm with a concentration of 10% can provide the best lip moisturizing effect to restore lip skin after 4 weeks. All lip balm preparations of Arabica coffee leaf extract do not irritate the skin. Lip balm preparation with 10% arabica coffee leaf extract concentration showed effectiveness as the best lip balm.